The Proceedings of the Coastal Sediments 2015 2015
DOI: 10.1142/9789814689977_0168
|View full text |Cite
|
Sign up to set email alerts
|

Field Observations of Tidal Flow Separation at a Mega-Scale Beach Nourishment

Abstract: Abstract:Large beach nourishments are often considered an efficient way to deal with coastal zone management issues, notably coastal erosion. Such large nourishments can act as a geometric perturbation, which might cause the tidal current to detach from the coastline. The Sand Motor is a mega-scale beach nourishment in the Netherlands. Field observations of the tidal flow field north of the Sand Motor are presented, showing evidence of flow separation and eddy formation during the flood phase of the tide. GPS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A sequence of these images can be found in Radermacher et al . [], but further analysis of the radar data is omitted here.…”
Section: Field Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…A sequence of these images can be found in Radermacher et al . [], but further analysis of the radar data is omitted here.…”
Section: Field Setupmentioning
confidence: 99%
“…In the time series of alongshore flow velocity, the influence of these forcing mechanisms is not visible, except for the positive peak during the late flood phase. As noted before, comparison with X‐band radar imagery [ Radermacher et al ., ] suggest that these peaks coincide with the arrival of the freshwater front.…”
Section: Numerical Model Setup and Comparison To Field Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to beach nourishments and regular shoreface nourishments, it has been shown that the Sand Motor has a size that is sufficient to significantly change the tidal currents. Field and model data presented by Radermacher et al (2015) and Radermacher et al (2017) show a large tidal eddy on either side of the Sand Motor. Grain size data presented by Huisman et al (2016) confirm the image, and it is also reproduced by the model (Luijendijk et al, 2017).…”
Section: Scale Effects Of Mega-nourishmentsmentioning
confidence: 95%
“…Regular shoreface nourishments are known to shift the area of wave breaking seaward and thereby modify longitudinal and crossshore sediment transport rates (van Rijn, 2011), but the effect is lasting for only a few years and little interference with tidal currents is usually observed because the nourishments are narrow and oriented in the direction of the tidal currents. In contrast, the Sand Motor has already been shown to significantly interfere with tidal currents, contracting the flow lines near the peninsula (Radermacher et al, 2015) and causing recirculating eddies at both sides in the residual flow. This influences nearby sediment sorting (Huisman et al, 2016) and diversifies the correlation structure between depth, waves, tidal current and sediment composition.…”
Section: Introductionmentioning
confidence: 99%